Genomic epidemiology and evolution of Bordetella pertussis under the vaccination pressure of acellular vaccines in Beijing, China, 2020–2023 - Zhen Li; Fei Xiao; Yue Hou; Bin Jia; Ji Zhuang; Yang Cao; Jianxin Ma; Jianhong Zhao; Zengquan Xu; Zhe Jia; Fang Liu; Lin Pang; et al. (Emerging Microbes and Infections)
Pertussis (or whooping cough) has experienced a global resurgence despite widespread vaccine efforts. In China, the incidence of pertussis has rapidly increased, particularly following the COVID-19 pandemic. Whole-genome sequencing analysis was performed on 60 Bordetella pertussis strains isolated in Beijing from 2020–2023, and the sequences were compared with those of 635 strains from China and 943 strains from other countries. In this study, the genetic evolution of B. pertussis was investigated, focusing on key virulence genes (ptxP, ptxA, prn, fim2, fim3, tcfA) and the resistance-related locus A2047 across different periods and regions. The dominant antigen genotype among the 60 isolates was ptxP3/prn2/ptxA1/fim2-1/fim3-1/tcfA2 (88.3%), differing from the prevalent genotype ptxP-1/prn-1/ptxA-1 in Beijing prior to 2019 and the vaccine strain genotype ptxP-1/prn-1/ptxA-2/fim2-1/fim3-1/tcfA2. Evolutionary analysis revealed significant genetic shifts associated with the introduction of vaccines, particularly acellular vaccines. Initially, the prevalent genotypes included ptxP-1, prn-1, ptxA-2, fim2-2, and fim3-2. However, currently, ptxP-3, prn-2 and ptxA-1 have become predominant globally, indicating vaccine-induced selection pressure. Additionally, all 60 isolated strains (100%) presented the A2047G mutation associated with erythromycin resistance, of which ptxP3 accounted for 91.7%. Macrolide-resistant Bordetella pertussis (MRBP) is widespread in China, and the prevalence of ptxP3-MRBP may be increasing. The significant changes of dominance of subtypes in Beijing in recent years underscore the need for continuous surveillance and adaptation of pertussis vaccination strategies.